Impact of neoadjuvant therapy on cancer-associated fibroblasts in rectal cancer. Issue 3 (September 2015) - Verset, Laurine; Tommelein, Joke; Moles Lopez, Xavier; Decaestecker, Christine; Boterberg, Tom; De Vlieghere, Elly; Salmon, Isabelle; Mareel, Marc; Bracke, Marc; De Wever, Olivier; Demetter, Pieter
Abstract Background and purpose Cancer-associated fibroblasts (CAFs) are increasingly recognised as promoters of tumour progression. It is poorly investigated whether cancer management protocols, such as neoadjuvant radio(chemo)therapy, have an impact on CAFs and, by consequence, on tumour progression. This prompted us to study the impact of neoadjuvant radio(chemo)therapy on the α-SMA/epithelial area ratio in rectal cancer, and the impact of this ratio on recurrence-free survival. Material and methods Immunohistochemistry for the CAF marker α-SMA and the proliferation marker Ki67 was performed on sections from 98 rectal cancers of which 62 had undergone neoadjuvant radio(chemo)therapy. Results Computer-assisted quantitative analysis showed that the α-SMA/neoplastic epithelial area ratio was higher after neoadjuvant therapy, and that rectal cancers with high α-SMA/epithelial area ratio had low proliferation rates. Interestingly, the α-SMA/epithelial area ratio was an adverse prognostic factor with regard to recurrence-free survival in univariate analysis. In addition, multivariate analysis showed that an α-SMA/epithelial area ratio above 1 provides an independent prognostic value associated with a poor recurrence-free survival. Conclusion These results suggest that neoadjuvant treatment has an impact on CAFs in rectal cancer. The correlation of CAFs with decreased recurrence-free survival and abundant experimental data in the literature suggest that under certain circumstances, not yet very well understood, CAFs may favour tumour progression.